2020
DOI: 10.1038/s41598-020-78083-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases for attenuation of morphine withdrawal by Heantos-4: role of l-tetrahydropalmatine

Abstract: Severe withdrawal symptoms triggered by cessation of long-term opioid use deter many individuals from seeking treatment. Opioid substitution and α2-adrenergic agonists are the current standard of pharmacotherapy for opioid use disorder in western medicine; however, each is associated with significant complications. Heantos-4 is a non-opioid botanical formulation used to facilitate opioid detoxification in Vietnam. While ongoing clinical use continues to validate its safety and effectiveness, a mechanism of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 79 publications
(129 reference statements)
2
17
0
Order By: Relevance
“…Treatment with THP blocks the morphine-induced downregulation of dopamine D2 receptors (D 2 R) and upregulation of GluA1 AMPA receptors in the prefrontal cortex, hippocampus (Hip), and striatum. THP inhibits dopamine-induced dopamine D1 receptor (D 1 R) activity and dopamine autoreceptor activity ( Wu et al, 2018 ; Ahn et al, 2020 ). These results suggest that the possible mechanism may be linked to antagonizing morphine-induced changes in brain dopamine and glutamate transmission.…”
Section: Pharmacological Activities Of Tetrahydropalmatinementioning
confidence: 99%
“…Treatment with THP blocks the morphine-induced downregulation of dopamine D2 receptors (D 2 R) and upregulation of GluA1 AMPA receptors in the prefrontal cortex, hippocampus (Hip), and striatum. THP inhibits dopamine-induced dopamine D1 receptor (D 1 R) activity and dopamine autoreceptor activity ( Wu et al, 2018 ; Ahn et al, 2020 ). These results suggest that the possible mechanism may be linked to antagonizing morphine-induced changes in brain dopamine and glutamate transmission.…”
Section: Pharmacological Activities Of Tetrahydropalmatinementioning
confidence: 99%
“…Consistent with this view, earlier in vivo microdialysis studies conducted in opioid‐dependent animals demonstrated that naloxone induces somatic withdrawal signs and suppresses DA levels in the ventral striatum for several hours (Pothos et al, 1991; Rossetti et al, 1992; Spanagel et al, 1994; Stella et al, 2003; Zhou & Nyberg, 2002) (but see Silverstone et al, 1993), findings that were confirmed again by recent in vivo monitoring studies (Ahn et al, 2020; Dias et al, 2016; Fox et al, 2017). In contrast, a recent reanalysis of [ 11 C]raclopride‐positron emission tomography (PET) scans of chronic opioid users failed to detect a significant decrease (or increase) in DA release in the human ventral striatum following naloxone administration (Shokri‐Kojori et al, 2021), a finding that challenges existing preclinical evidence.…”
Section: Introductionmentioning
confidence: 60%
“…Specifically, attenuation of dopaminergic function, or hypodopaminergia , in the ventral striatum is hypothesized to contribute to the aversive state associated with opioid withdrawal (Kakko et al, 2019; Koob, 2021; Melis et al, 2005). Furthermore, a ‘reset’ of the hypodopaminergic state in the ventral striatum is proposed as a therapeutic approach for managing opioid withdrawal symptoms and facilitating detoxification from opioids (Ahn et al, 2020; Koob, 2021; Melis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Notable recent examples include the development of the opioid detoxification product Heantos-4 by a traditional Vietnamese herbalist, Tran Khuong Dan, who tested his method by addicting himself first to opium and then heroin, confirming the efficacy of his invention based on twelve non-toxic, non-addictive herbal components (Turkia, 2021). Tetrahydroprotoberberines were later identified as the most likely active ingredients (Ahn et al, 2020;Nesbit and Phillips, 2020).…”
Section: The Practice Of Self-experimentationmentioning
confidence: 99%